The new organizational form of rehabilitation for mentally ill patients - a complex «a round-the-clock hospital (with the open doors)-a day time hospital - A. P. Kotsiubinsky; B. G. Butoma (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева, 2018)
Among factors contributing to the non-verbal behavior of the patient and, therefore, aimed at the social vector of the effectiveness of the treatment, a significant role is played by the so-called «geometry of social space». The destruction of the stereotypes of behavior in the framework of certain personal-territorial interactions (which occurs when transferring the patient from one department to another) and the need for the patient to create new interactions between other patients in the changed spatial hierarchy may lead to a deterioration in the patient’s condition (in a result of «psychological trauma» reduced his social competence. Noted above is substantially leveled at the organization complex «a round-the-clock hospital (with the open doors) - a day time hospital». Creating such a complex promotes to conservation of these psychological constructs or psychological sovereignty of the patient, i.e., to his/her existence as a full body-territorial and existential unity, maintains or improves his/her adaptation-compensatory mechanisms and, therefore leads to successful biopsychosocial rehabilitation. Proposed a new model of organization of psychiatric service a complex «a round-the-clock hospital (with the open doors) - a day time hospital» requires further investigations and accumulation of facts to clarify the precise criteria for the work of the structure and formation of the corresponding legal standards of its existence.